The Estimated Amount, Nutrition, and Economies of Food loss and Food waste for Food Security in West Java - Putri Nur Fatimah; Yayuk Farida Baliwati (Media Gizi Indonesia, 2022)
One of the challenges in food security is the high amount of food loss and food waste. Reducing food loss and food waste in half along the food chain is part of the twelfth SDGs goal. Based on data from The Economist Intelligence Unit (EIU) in 2017, Indonesia was the second highest ranked country with an FLW of 300 kg/person/year. West Java is the province with the highest population in Indonesia and plays an important role in meeting national food needs so that sufficient food availability is required. This study aims to analyze food loss and food waste for food security in West Java. While the specific objectives of this study are to estimate the amount of food loss and strategic food waste in each food chain in West Java, and macronutrients and economic losses from FLW. This study utilizes secondary data with a quantitative descriptive analysis design. The method of calculating food loss and waste uses the formula for the estimated percentage of food loss and waste in South and Southeast Asia by the FAO. The results of this study indicate the estimated total food loss and strategic food waste in West Java in 2018 was 2,04 million tons. In addition, food loss and waste cause a loss of nutritional content such as energy of 335,61 kcal/day, protein of 9,38 grams/day and fat of 3,98 grams/day as well as economic losses of 32,89 trillion rupiah. Food loss and waste must be reduced for greater food security.